Construction and Release Characteristics of 3D Printed Spaced Multi-layer Structure of Lutein Emulsion Gel - Shuai DENG; Minghui ZHAO; Chunxue HAO; Ming LI; Dajing LI; Lei FENG; Zhongyuan ZHANG; Yayuan XU (Shipin gongye ke-ji)
In this study, 3D printing technology with double nozzles was applied to print lutein emulsion gels (lutein-loaded layer) and corresponding unloaded emulsion gels in an interlaced manner. The preparation parameters of lutein-loaded and unloaded emulsion gels were screened by evaluating the rheological properties and 3D printing characteristics. 3D printed gel systems with different intervals of multilayers structures were constructed to explore the effects of the number of spacer layers and the positioning of empty layers in spaced multi-layer structures on the release characteristics and bioaccessibility of lutein. The results indicated that increasing the oil phase volume fraction, separating the concentration of whey protein isolate (WPI), and loading of lutein could effectively enhance the apparent viscosity, storage modulus, and loss modulus of lutein emulsion gels. Simultaneously, it reduced creep recovery strain, strengthened the viscoelasticity of lutein emulsion gels, and improved their resistance to deformation, thereby significantly enhanced the printing accuracy and stability of lutein emulsion gels. When the oil phase volume fraction was 15%, the WPI concentration was 10% and the lutein loading was 1.5%, the lutein emulsion gel showed the best 3D printing results, with printing accuracy and stability of 96.94% and 97.60%, respectively. After simulated digestion in vitro, the interval multi-layer structure could effectively change the release behavior of lutein, significantly reducing the release rate of lutein in the gastric digestion stage from 21.61% to 7.26% at the lowest. Furthermore, the release curve of lutein showed a certain time lag in the intestinal digestion stage, and significantly improving the bioaccessibility of lutein, reaching a maximum of 47.97%. The project will provide new ideas and theoretical basis for solving the bottleneck problem of lutein low bioaccessibility and the design of delivery vehicles.